PENGARUH PENGGUNAAN E-MODUL FLIPBOOK TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR PADA PEMBELAJARAN IPA - Raudhotul Jannah; Vira Amelia; Darmansyah; Yanti Fitria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
This study aims to determine the effect of using E-module flipbook on elementary school students' learning outcomes in science subjects. This research uses a qualitative method that describes and describes the effect of using E-module flipbook on the learning outcomes of elementary school students. The data in this study were collected using literature study techniques in which the collection of materials related to this research was sourced from books, journals, literature, and other appropriate and relevant publications. Researchers will describe and analyze the data. Research variables are everything that researchers choose to research which aims to learn more, collect related data, and draw conclusions. In this study using dependent variables and independent variables ... The author hopes to use quantitative research methods in order to provide information about the facts about the effect of using flipbook e-modules on the learning outcomes of elementary school students in science subjects. Keywords: E-module, Flipbook, IPA